The Use of Violence in Indonesian Police Investigation - Abdurrachman, Hamidah; Ari Sudewo, Fajar (International Journal of Engineering and Technology, 2018)
The tricky part of the investigation process in Indonesian Criminal Justice System is to balance the requirement to successfully uncover cases reported by the public while at the same time avoiding a violation of Human Rights at all cost. To do their duty, the police as investigators are given the authority to take measures such as arrest, detention, search, seizure and examination of letters. In implementing these forceful measures, the tendency of abuse to occur is highly likely, including but not limited on the use of violence to intimidate, evidence engineering, false arrests, maladministration, and other forms of human rights violation. Some of the stages within the investigation process that often use violence as a means to an end are during arresting, interrogating, investigating, and giving detention to suspects. The form of violence in use includes physical and psychological ones, with one of the most extreme examples involving the use of automatic weapon to inflict pain. This study is a result of an empirical research into the use of violence in Indonesian police investigation. We use primary and secondary data sources, including laws, literature, and doctrine, before analyzing the data qualitatively. This research is expected to contribute in further strengthening the principle of Due Process of Law in the implementation of the police investigation process. Even though the principle of Due Process of Law is well known in the Law on Criminal Proceedings of Indonesia, its application is still considered as weak. It is the contention of this paper that the principle of Due Process of Law should be included in the Police Chief Regulation and the regulations within the Code of Police. Â Â Â